From Claw Crane to Toy Crane: Catching, Courting, and Gambling in South Korea - Karhulahti Veli-Matti; Heljakka Katriina; Dongwon Jo (United States, 2022)
The claw crane—an arcade game that invites its players to remotely grab a prize with a “claw”—has undergone a long process of development from an eye-catching “steam shovel” to a calculated gambling machine across amusement arcades, train stations, and traveling carnivals. Recently, the claw crane has become a common transmedia object in various consumer outlets around the world, serving today’s “kidults” who are willing to play and be playful with toys as grownups. Especially in South Korea, the claw crane now rewards its players with cutified character plushies, which arguably reflects and resonates with the local sociocultural conventions. In this mixed-methods study, we deconstruct the claw crane as a historical artifact that promotes diverse forms of human interaction and engagement in the techno-cultural and social context of South Korea. The claw crane (or in South Korea, rather the “toy crane”) is investigated by means of historical design analysis, a review of contemporary South Korean media texts, and field observations in Seoul. We suggest the claw crane to serve as a multipurpose medium for playful interactions beyond the act of play itself—and in South Korea, having become a means for playful courting and emotional support, which at times of anxiety, stress, and uncertainty may contribute to one’s confidence and belief in the future.